Integrated multi-omics elucidates PRNP knockdown-mediated chemosensitization to gemcitabine in pancreatic ductal adenocarcinoma - Qi, Bing; Wu, Yuwei; Wang, Ning; Duan, Liumeng; Wei, Yangbo; Zhang, Xuanrui; Chen, Jing (Frontiers in Immunology, 2025)
IntroductionPancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy with an extremely poor prognosis. Gemcitabine (GEM), the standard first-line chemotherapeutic agent for PDAC, often fails due to the development of drug resistance. This study aims to systematically investigate the mechanisms underlying gemcitabine resistance in PDAC and identify novel therapeutic targets.MethodsWe integrated multi-omics data, including microarray, transcriptomic, proteomic, single-cell RNA sequencing, and spatial transcriptomic datasets. Machine learning algorithms were employed to screen for key genes associated with resistance. The correlation between candidate genes and drug-resistant phenotypes was inferred using pancreatic cancer cell lines, mouse models, and clinical patient data. Functional and mechanistic studies were subsequently conducted through in vitro cellular experiments.ResultsOur findings identify the prion protein gene (PRNP) as a key gene associated with chemoresistance. PRNP expression is significantly elevated in PDAC patients treated with gemcitabine and correlates with the resistant phenotype. Cellular experiments confirmed that gemcitabine exposure upregulates PRNP expression, while PRNP knockdown significantly reduces the half-maximal inhibitory concentration of gemcitabine and enhances its cytotoxicity. Mechanistic studies demonstrate that PRNP drives resistance through dual pathways: it promotes epithelial-mesenchymal transition (EMT), enhancing cellular invasiveness, and suppresses ferroptosis by upregulating the expression of ferroptosis-related proteins SLC7A11 and GPX4, thereby maintaining redox homeostasis. Further single-cell and spatial transcriptomic analyses revealed that PRNP is predominantly enriched in a specific subset of cancer-associated fibroblasts (CAFs) following chemotherapy, which is associated with the establishment of an immunosuppressive tumor microenvironment.DiscussionThis study demonstrates that PRNP is a key regulator of gemcitabine resistance in PDAC, modulating EMT, ferroptosis, and the tumor immune microenvironment. Targeting PRNP represents a promising therapeutic strategy to reverse gemcitabine resistance and may hold significant potential for clinical translation in PDAC treatment.